Perception of the Role of Fintech on Formal Workers During the COVID-19 Pandemic (Study on Construction Workers) - Lukiyanto, Kukuh; Trisilia, Meilinda; Vinanti, Siona; Wijayaningtyas, Maranatha (KnE Social Sciences, 2024)
The development of FinTech in Indonesia has had many good impacts, not only for the company but also for the employees within it. Especially during the COVID-19 pandemic, which resulted in limited outdoor mobility. This study aimed to understand the effectiveness of FinTech for formal workers during the COVID-19 pandemic. The qualitative descriptive study was a case study of 40 employees at a construction company in Surabaya. The results of the study showed that FinTech plays an important role for formal workers in companies, including efficiency and facilitating financial services, facilitating funding and transactions, improving the standard of living of employees, as well as planning future investments for the formal workers themselves. Keywords: financial technologist, covid19 pandemic, formal workers